Indoglish in Naturally Occurring Post Class Peer Talk: Structural Patterning and Interactional Functions among Master EFL Learners - Ahmad Yugita Ishaq; Evyurul Laily Zen; Nurenzia Yannuar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Research on Indoglish has largely concentrated on social media discourse, written language practices, and broad educational setting, remaining spontaneous peer interaction comparatively underexplored. Addressing this gap, this study examines Indoglish as natural peer talk in post class discussion among master’s students. By applying a qualitative sociolinguistic design, the study draws on naturally occurring spoken interaction recorded after class amd transcribed using Turboscribe. The dataset consists of nine audio recordings, involving 20 EFL master students , with each recording lasting approximately 20-30 minutes. The data were investigated to identify recurrent structural patterns in bilingual utterances and to define their sociolinguistic sig in context The findings reveal three fundamental patterns: Indonesian Matrix with English insertion, Hybrid or mixed framed structures, and English Matrix with Indonesian insertion. These patterns prove that Indoglish in post class peer discussion is not a random alternation of linguistic elements, but systematic and interactionally meaningful practice. The analysis further reveals that such bilingual patterning allows learners to negotiate meaning, express stance, maintain interactional flow, and strengthen peer solidarity in informal academic discourse. By shifting attention from predominantly written and digitally mediated indoglish to naturally occurring spoken discourse, this study contributes to the sociolinguistic comprehending of bilingual language practice among EFL learners and highlight post class peer discussion as a productive site for investigating multilingual meaning making.